MODEL MANAJEMEN HUBUNGAN MASYARAKAT (HUMAS) BERBASIS WEBSITE PENGOLAHAN INFORMASI PUBLIK DI DINAS KOMUNIKASI DAN INFORMATIKA KABUPATEN BONE BOLANGO - Pakaya, Abdul Kadir; Suprapto, Srihandayani; Akbar, Muh. Firyal (Gapenas Publisher, 2025)
This study aims to examine the Website-Based Public Relations Management Model (PR) in public information management at the Communication and Information Office of Bone Bolango Regency. The research uses a descriptive qualitative method. This study found that the applied model is not fully optimal. In terms of planning, the Agency has prepared a plan for delivering public information, mapping the needs of the community, and planning website development and how to overcome the shortage of information management human resources. This step answers problems related to the lack of human resources and public relations training that has not been routinely carried out. The organizational indicators are also quite good. The agency has established a website management team structure, dividing roles between information managers, IT teams, and public relations teams, and involving various parties in the information delivery process. However, in implementation, the results are still not optimal. Information has not been conveyed evenly, especially in blank spot areas and areas without WiFi access. Although social media and portals have been used effectively, routine training for the PR team has not yet been implemented. In the evaluation, the Agency does not yet have a comprehensive system to measure the effectiveness of information delivery, even though success indicators have been prepared. This obstacle needs to be overcome to improve the quality of public information management